Perbanyakan gembili (Dioscorea esculenta) menggunakan setek batang - Mariay, Ivonne Fitria; Amriati, Besse; Juniastri, Eti (Agrotek, 2023)
This research aims to determine the effect of stem cutting size on the growth of Gembili. The design used in this research was a Randomized Group Design (RAK) with 4 treatments repeated 3 times. The research treatments were M1 = cutting length 20 cm, M2 = cutting length 30 cm, M3 = cutting length 40 cm, and M4 = cutting length 50 cm. Data analysis uses variance, if the treatment has a significant effect, then the analysis continues using the Least Significant Difference test (LSD) with a confidence level of 95%. The results showed that the size of the cuttings had no significant effect on the growth of Gembili in all growth variables. The length of cuttings of 50 cm tended to show the highest increase in average values for all observed growth variables.